GANGGUAN PERTUMBUHAN DAN DEFISIT BERAT BADAN PADA BALITA DI PERKOTAAN DAN PEDESAAN - Muljati, Sri; Hapsari, Dwi; Budiman, Basuki (PERSATUAN AHLI GIZI INDONESIA, 2005)
GROWTH FAILURE AND BODY WEIGHT DEFICIT OF UNDERFIVE CHILDREN IN URBAN AND RURAL AREASThe prevalence of malnutrition in Indonesia in 2003 is 19 percents; three percents of them are severe malnutrition. Study on the age beginning deviation of growth failure and the extent of the deficit in body weight of underfive children in Indonesia is scarce. We analysed 1694 records of children underfive year old from National Household Survey (SKRT) having complete data in weight, height and age. The study revealed that 42.9% children underfives suffered from growth failure, in which the magnitude was greater in rural than urban e.i. 53.8% and 46.2% respectively growth failure started. In the age 4 months, infant begins deficit his her body weight and the peak of the deficit is infant in six months e.i 21.05%. This analysis supports international finding that deviation in growth failure begin at 4 month for Indonesian children should be consideredKeywords: under five year children, growth